A comparison of clinicians' racial biases in the United States and France. (June 2018) - Khosla, Natalia N.; Perry, Sylvia P.; Moss-Racusin, Corinne A.; Burke, Sara E.; Dovidio, John F.
Abstract: Rationale: Clinician bias contributes to racial disparities in healthcare, but its effects may be indirect and culturally specific. Objective: The present work aims to investigate clinicians' perceptions of Black versus White patients' personal responsibility for their health, whether this variable predicts racial bias against Black patients, and whether this effect differs between the U.S. and France. Method: American ( N = 83) and French ( N = 81) clinicians were randomly assigned to report their impressions of an identical Black or White male patient based on a physician's notes. We measured clinicians' views of the patient's anticipated improvement and adherence to treatment and their perceptions concerning how personally responsible the patient was for his health. Results: Whereas French clinicians did not exhibit significant racial bias on the measures of interest, American clinicians rated a hypothetical White patient, compared to an identical Black patient, as significantly more likely to improve, adhere to treatment, and be personally responsible for his health. Moreover, in the U.S., personal responsibility mediated the racial difference in expected improvement, such that as the White patient was seen as more personally responsible for his health, he was also viewed as more likely to improve. Conclusion: The present work indicates that American clinicians displayed less optimistic expectations for the medical treatment and health of a Black male patient, relative to a White male patient, and that this racial bias was related to their view of the Black patient as being less personally responsible for his health relative to the White patient. French clinicians did not show this pattern of racial bias, suggesting the importance of considering cultural influences for understanding racial biases in healthcare and health. Highlights: U.S. medical clinicians expect White patient to benefit more from care than Black. U.S. clinicians see White patient as more personally responsible for health. White patient expected to benefit more because seen as more personally responsible. In France, no racial difference in patient expectations or personal responsibility. Increasing clinician awareness of own racial bias important to reduce disparities.